Long-Term Safety and Efficacy of Durable Polymer Cobalt-Chromium Everolimus-Eluting Stents in Patients at High Bleeding Risk: A Patient-Level Stratified Analysis From Four Postapproval Studies. Issue 11 (17th March 2020) - Sorrentino, Sabato; Claessen, Bimmer E.; Chandiramani, Rishi; Guedeney, Paul; Vogel, Birgit; Baber, Usman; Rau, Vinuta; Wang, Jin; Krucoff, Mitchell; Kozuma, Ken; Ge, Junbo; Seth, Ashok; et al.
Abstract : Background: Long-term outcomes in patients at high bleeding risk (HBR) undergoing percutaneous coronary intervention with a drug-eluting stent are unclear. Therefore, we aimed to evaluate long-term adverse events in HBR patients undergoing percutaneous coronary intervention with cobalt-chromium everolimus-eluting stent implantation. Methods: We analyzed stratified data from 4 all-comers postapproval registries. Patients with at least 1 of the following criteria were categorized as HBR: age ≥75 years, history of major bleeding (MB), history of stroke, chronic oral anticoagulant use, chronic kidney disease, anemia, or thrombocytopenia. Additionally, in a separate analysis, patients were categorized according to the recently published Academic Research Consortium HBR criteria. The Kaplan-Meier method was used for time-to-event analyses. Coronary thrombotic events (CTE) included myocardial infarction or definite/probable stent thrombosis. MB was defined according to the TIMI (Thrombolysis in Myocardial Infarction) or GUSTO (Global Use of Strategies to Open Occluded Coronary Arteries) scales. Impact of CTE and MB on subsequent risk of mortality was assessed using multivariable Cox regression with MB and CTE included as time-updated covariates. Results: Of the total 10 502 patients included, 3507 (33%) were identified as HBR. Compared with non-HBR patients, those at HBR had more comorbidities, higher lesion complexity, and a higher risk of 4-year mortality (Hazard Ratio [HR] 4.38 [95% CI, 3.76–5.11]). Results were qualitatively similar when using Academic Research Consortium criteria to define HBR. Risk of mortality was increased after CTE (HR 5.02 [95% CI, 3.93–6.41]), as well as after MB (HR 4.92 [95% CI, 3.82–6.35]). Of note, this effect was consistent across the spectrum of bleeding risk ( P -interaction test 0.97 and 0.06, respectively). Conclusions: Compared with the non-HBR population, HBR patients experienced worse 4-year outcomes after percutaneous coronary intervention with cobalt-chromium everolimus-eluting stent. Both CTE and MB had a significant impact on subsequent risk of mortality irrespective of bleeding risk. Abstract : Supplemental Digital Content is available in the text.